Autotaxin in ascites promotes peritoneal dissemination in pancreatic cancer. Issue 2 (21st December 2020) - Jinno, Naruomi; Yoshida, Michihiro; Hayashi, Kazuki; Naitoh, Itaru; Hori, Yasuki; Natsume, Makoto; Kato, Akihisa; Kachi, Kenta; Asano, Go; Atsuta, Naoki; Sahashi, Hidenori; Kataoka, Hiromi
Abstract: Peritoneal dissemination and malignant ascites in pancreatic ductal adenocarcinoma (PDAC) patients represent a major clinical issue. Lysophosphatidic acid (LPA) is a lipid mediator that modulates the progression of various cancers. Based on the increasing evidence showing that LPA is abundant in malignant ascites, we focused on autotaxin (ATX), which is a secreted enzyme that is important for the production of LPA. This study aimed to elucidate the importance of the ATX‐LPA axis in malignant ascites in PDAC and to determine whether ATX works as a molecular target for treating peritoneal dissemination. In a PDAC peritoneal dissemination mouse model, the amount of ATX was significantly higher in ascites than in serum. An in vitro study using two PDAC cell lines, AsPC‐1 and PANC‐1, showed that ATX‐LPA signaling promoted cancer cell migration via the activation of the downstream signaling, and this increased cell migration was suppressed by an ATX inhibitor, PF‐8380. An in vivo study showed that PF‐8380 suppressed peritoneal dissemination and decreased malignant ascites, and these results were validated by the biological analysis as well as the in vitro study. Moreover, there was a positive correlation between the amount of ATX in ascites and the degree of disseminated cancer progression. These findings demonstrated that ATX in ascites works as a promotor of peritoneal dissemination, and the targeting of ATX must represent a useful and novel therapy for peritoneal dissemination of PDAC. Abstract : We could detect the strong inhibitory effect of PF‐8380 on intraperitoneal dissemination of pancreatic ductal adenocarcinoma (PDAC) as it was clearly visualized by bioluminescence imaging and under white‐light imaging.